Sirtuin 1 and Aging Theory for Chronic Obstructive Pulmonary Disease. (5th July 2015) - Conti, V.; Corbi, G.; Manzo, V.; Pelaia, G.; Filippelli, A.; Vatrella, A.
Abstract : Chronic Obstructive Pulmonary disease (COPD) is an inflammatory syndrome that represents an increasing health problem, especially in the elderly population. Drug therapies are symptomatic and inadequate to contrast disease progression and mortality. Thus, there is an urgent need to clarify the molecular mechanisms responsible for this condition in order to identify new biomarkers and therapeutic targets. Processes including oxidant/antioxidant, protease/antiprotease, and proliferative/antiproliferative balance and control of inflammatory response become dysfunctional during aging as well as in COPD. Recently it was suggested that Sirtuin 1 (SIRT1), an antiaging molecule involved in the response to oxidative stress and chronic inflammation, is implicated in both development and progression of COPD. The present review focuses on the involvement of SIRT1 in the regulation of redox state, inflammation, and premature senescence, all crucial characteristics of COPD phenotypes. Recent evidence corroborating the statement of the "aging theory for COPD" was also discussed.